2011
DOI: 10.1177/0098628311401585
|View full text |Cite
|
Sign up to set email alerts
|

Now or Later?

Abstract: This study used a national sample of PhD students in clinical psychology (N ¼ 1,034) to explore when students decided to pursue their graduate degree, reasons for their decisions, and associated satisfaction. Results indicated that immediately after completing their undergraduate degree, 57% of current graduate students reported postponing graduate studies, 10% went directly to a terminal master's program, and 33% went directly to a clinical psychology PhD program. A variety of reasons for these decisions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Additionally, graduate school alumni discussed goals and readiness for next steps more than workforce alumni. Zimak et al (2011) also found that students directly entering graduate school were more certain about goals and felt more prepared relative to peers who delayed graduate school.…”
Section: Graduate School Alumnimentioning
confidence: 86%
See 4 more Smart Citations
“…Additionally, graduate school alumni discussed goals and readiness for next steps more than workforce alumni. Zimak et al (2011) also found that students directly entering graduate school were more certain about goals and felt more prepared relative to peers who delayed graduate school.…”
Section: Graduate School Alumnimentioning
confidence: 86%
“…Additionally, many workforce alumni described uncertainty about graduate school. Uncertainty regarding graduate school may be associated with gaining more experience and applying to graduate school in the future (Zimak et al, 2011). Workforce alumni described identities related to ending time decision making.…”
Section: Workforce Alumnimentioning
confidence: 99%
See 3 more Smart Citations